Characterization and strength activity index of eco-processed pozzolan - Abraham Henry Bernard; Ahmad Nurfaidhi Rizalman (International Islamic University Malaysia, 2025)
Eco-processed pozzolan (EPP) is a newly emerging pozzolanic material produced from the extraction, refinement, and calcination of spent bleaching earth. Due to its pozzolanic characteristics, EPP is a novel interest in the material sustainability of concrete technology in Malaysia today. However, there is still a lack of studies on how much EPP replacement fulfills the minimum requirements of 75% of the value of the strength activity index (SAI) as specified in the ASTM C618 standard. This study investigated the chemical, physical, mineralogical, and microstructural properties of EPP. The results revealed that EPP fulfilled the criteria as a class N pozzolan as per ASTM C618. According to the XRD result, the mineralogical data suggest that the OPC has a high amount of alite and belite at 65.65% and 10.26%, respectively. In contrast, the EPP showed high amorphous silica at 64.28%. Based on the scanning electron microscopy (SEM) images, the EPP particles had a spherical and porous structure, which increased the amount of water required for the mortar containing EPP. This study also examined EPP's strength activity index (SAI) at 10%, 20%, 30%, 40%, 50%, and 60% as partial cement replacement. The results indicated that the SAI was reduced with high EPP replacement percentages due to lower CaO content. The 28-day SAI value satisfied the minimum requirement of pozzolan as per ASTM C618 for cement replacement by up to 40%. In conclusion, EPP performed well as a cementitious supplementary material, with 10% and 20% being optimal replacements for cement.